2006
DOI: 10.1111/j.1525-1497.2006.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction of female and male users of veterans health administration services

Abstract: After adjustment for patient attributes, female VHA outpatients report similar OQ with VHA services as male patients. The fact that some inpatient dimensions of satisfaction continued to show effects favoring males even after adjustment suggests areas for continued focus in improving health care quality. Covariate adjustment is essential for evaluating satisfaction with health care services. Breaking down overall satisfaction into independent aspects of services is useful. The SHEP survey has provided a useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 25 publications
1
96
1
Order By: Relevance
“…This item asked participants to rate the effectiveness of their pain treatment on a five-point scale from "poor" to "excellent." SHEP is used for VA quality improvement and is based on measures developed by the Picker Institute (Camden, Maine), and was subsequently refined based on veteran focus groups [40]. We used these two measures independently in analyses as two different aspects of treatment satisfaction.…”
Section: Treatment Satisfactionmentioning
confidence: 99%
“…This item asked participants to rate the effectiveness of their pain treatment on a five-point scale from "poor" to "excellent." SHEP is used for VA quality improvement and is based on measures developed by the Picker Institute (Camden, Maine), and was subsequently refined based on veteran focus groups [40]. We used these two measures independently in analyses as two different aspects of treatment satisfaction.…”
Section: Treatment Satisfactionmentioning
confidence: 99%
“…The sampling strategy and logistics of the SHEP are described elsewhere. 16 The AUDIT-C consists of three questions and takes less than three minutes to administer (Online Appendix A). Each AUDIT-C response is scored 0 to 4, with total AUDIT-C scores ranging from 0 to 12.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Through a literature search, we identified several patient characteristics as a priori potential confounders and included those available from SHEP data as covariates based on their associations with receipt of brief interventions and patient-reported quality-of-care ratings. 31,34,37,[39][40][41] These included age, gender, race/ethnicity (non-Hispanic white, non-Hispanic black, Hispanic, or other), educational attainment (less than high school, high school, General Educational Development Test [GED], or 2-year degree; 4-year degree; or greater than 4-year degree), and Short Form-1 self-reported health status (poor, fair, good, very good, or excellent). In addition, we included severity of unhealthy alcohol use, as previous studies have demonstrated associations between greater alcohol consumption and receipt of brief interventions, 37,39,40 and severity may also be associated with patient-reported quality-of-care ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Weights were developed by the VA's Office of Analytics and Business Intelligence to account for sampling design and non-response related to age, gender, and clinical site. 31 Large weights were truncated at 500 to ensure individuals with outlying weights did not largely drive results (n=115). We used Stata version 12.0 (StataCorp LP, College Station, TX, USA) for all analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation